The Effects of Demonstration Teaching Method Combined with SimulationBased Learning Method on Nursing Students Ability to Perform Based on the Advanced Cardiovascular Life Support Standards and Satisfaction - Seangon, Laddawan; Songsithikul, Tararat; Puaviriyapant, Janya; Kunno, Nathaporn (Journal of The Royal Thai Army Nurses, 2021)
This quasi-experimental research examined the effects of demonstration teaching method combined with simulation-based learning on nursing students’ ability to perform according to advanced cardiovascular life support standards and their satisfaction on the teaching. The samples of this study were 80 third-year students from Bachelor of Nursing program that were divided into 40 students for an experimental and 40 students for a controlled group. The instruments included : (1) the general data questionnaire (2) the satisfaction questionnaire toward the teaching, (CVI value of .87) (3) the ability test on the advanced cardiovascular life support for critically ill patients, (CVI value of .83). and (4) the simulation case of critically ill patients and virtual simulation models. The statistics employed for this analysis were percentile, medium, standard deviation and t-test. The research results showed that: (1) the average score of nursing students’ ability to follow standard of resuscitation was significantly higher after learning through demonstration and simulation-based learning (significance level at .001); (2) according to the average score, the ability of the nursing students learnt through demonstration and simulation-based learning method to comply with the resuscitation standards was higher than that of those experienced normal methods (significance level at .001); and (3) the average score of overall nursing students’ satisfaction learnt through demonstration and simulation-based learning was the highest.